If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24+(78-x)=36
We move all terms to the left:
24+(78-x)-(36)=0
We add all the numbers together, and all the variables
(-1x+78)+24-36=0
We add all the numbers together, and all the variables
(-1x+78)-12=0
We get rid of parentheses
-1x+78-12=0
We add all the numbers together, and all the variables
-1x+66=0
We move all terms containing x to the left, all other terms to the right
-x=-66
x=-66/-1
x=+66
| 25-5a=-5a-20 | | -3(v+6)=2v-33 | | x+106=x+74 | | 72-x=26 | | –2b+7=–4b−15 | | 2(3x4)=4x+32 | | 3-(7-3x)=2x+2 | | x+74=x+106 | | 3.5x-3=6x-8 | | 42+5y-13=16y-11-3y | | 19+x=62 | | -4x+2(x-6)=2 | | +12h+h2+27=0 | | 3x+9+4x-7=21 | | 85-(14+x)=68 | | 8(c–9)=6(2c–12)-4c | | 5(x6)=100 | | 1/2x-7=3(x-4)+3 | | -4x+2(x-6)=6 | | (68-x)+16=24 | | 88=8(z+1) | | y2-16y+64=0 | | 3m−9=–3 | | 2(3x-2)=41 | | 7(y-3)+y=9 | | 2x-22=-7(x+7) | | 86-x=39 | | 6x-12+6x-12=4x+8 | | −8x−8=16 | | 6r-7=23r= | | x-67=41 | | 4v-33=-v+23 |